Testis - a novel storage site in human cholesteryl ester storage disease. Autopsy report of an adult case with a long-standing subclinical course complicated by accelerated atherosclerosis and liver carcinoma - Elleder, M; Chlumska, A; Ledvinová, J; Poupetová, H (Virchows Archiv, 2000)
A case of long-standing subclinical cholesteryl ester storage disease (CESD) manifesting as hyperlipoproteinaemia type IIb without any hepatomegaly is described. The patient underwent surgical vascular interventions because of accelerated atherosclerosis, which dominated his middle age. CESD was an incidental finding when a liver biopsy specimen was taken because liver malignancy was suspected; the patient's condition proved to be due to a cholangiocarcinoma, which led to his death at the of age 52. The autopsy showed moderate-intensity storage in the set of cells characterized by constitutional high-level receptor-mediated LDL endocytosis (hepatocytes, adrenal cortical cells) and also revealed storage in the Leydig cells. The severity with which histiocytes were affected varied regionally, ranging from minimal detectable storage or none at all (gut, lymph nodes, spleen) to extreme lysosomal expansion by cholesteryl ester liquid crystals (bone marrow) or by ceroid (lung, testicular stroma), or by both (liver). The density of the histiocytic population did not correlate with the degree to which parenchymal cells were affected except in the testicular stroma, where it was prominent. The patient was a mixed heterozygote for the G934A and DeltaC(673-5) mutations.
Keywords: nádory žlučových cest; arterioskleróza; Bile Duct Neoplasms; mužské pohlaví; Arteriosclerosis; Male; nemoc ze střádání esterů cholesterolu; lyzozomy; Cholangiocarcinoma; Lysosomes; Humans; Fatal Outcome; Leydig Cells; nemoci varlat; lidé; Hyperlipoproteinemia Type II; Chromatography, Thin Layer; Middle Aged; lidé středního věku; Testicular Diseases; Cholesterol Ester Storage Disease; chromatografie na tenké vrstvě; Bile Ducts, Intrahepatic; Leydigovy buňky; lipasa; fatální výsledek; žlučové cesty intrahepatální; cholangiokarcinom; dospělí; Adult; Lipase; hyperlipoproteinemie typ II